"Tools in the Hand of God": Thomas Merton's Influence upon Henri J. M. Nouwen (part two) - Twomey, Gerald S. (Cistercian studies quarterly, 2009)
The article discusses the life of Thomas Merton, a catholic writer and social activist, and his influence on the works of Dutch catholic priest and writer, Henri J. M. Nouwen. Merton had deep solidarity for Latin America and his deepest religious experience took place when he returned to Havana, Cuba. In late 1950s, he promoted the work of Latin American beat poets. Nouwen believed that his essays on peace and racial equality were deeply influenced by Merton's thinking.